Assessing Insecticide Susceptibility and Resistance Intensity of Anopheles gambiae s.l. Populations From Some Districts of Benin Republic, West Africa. Issue 3 (31st March 2022) - Kpanou, Casimir Dossou; Sagbohan, Hermann W; Sovi, Arthur; Osse, Razaki; Padonou, Gil G; Salako, Albert; Tokponnon, Filémon; Fassinou, Arsène Jacques; Yovogan, Boulais; Nwangwu, Udoka C; Adoha, Constantin J; Odjo, Esdras Mahoutin; et al.
Abstract: Pyrethroid resistance is widespread in sub-Saharan Africa. The objective of this study was to assess the insecticide resistance intensity in Anopheles gambiae s.l. (Diptera: Culicidae) in four districts of Benin in order to better understand how pyrethroid-only nets are likely to be effective. Thus, adult females of An. gambiae s.l., reared from field-collected larvae were used for assessing resistance intensity to permethrin and deltamethrin. They were tested at 1×, 5×, and 10× the diagnostic dose, using both WHO susceptibility tube testing and CDC bottle bioassays. Identification of molecular species, as well as of L1014F Kdr and Ace -1 R mutations was performed using the PCR. The level of expression of biochemical enzymes was also evaluated. Overall, moderate to high resistance intensity to permethrin and deltamethrin was observed, irrespective of the testing method. While the L1014F Kdr frequency was high (>75%), Ace -1 R was low (≤6%) in An. gambiae s.s. and Anopheles coluzzii, the two predominant species [52% (95% CI: 44.8–59.1) and 45% (95% CI: 38.0–52.2), respectively]. Anopheles arabiensis was found at very low frequency (3%, 95%CI: 1.1–6.4). For Biochemical analyses, α and β-esterases were over-expressed in all four districts, while mixed-function oxidases (MFOs) were over-expressed in only one. Overall, the two testing methods led to comparable conclusions, though there were a few inconsistencies between them. The moderate-high resistance intensity observed in the study area suggests that dual active-ingredient (AI) long-lasting insecticidal nets (LLINs) may provide better control of insecticide-resistant mosquitoes.